Upaya Penggunaan Buku Pop Up Untuk Meningkatkan Kemampuan Literasi Membaca Siswa - Niswatul Hasanah; Siti Zulfiana; Zuri Anggraini (Journal of Teaching and Elementary Education, 2025)
Introduction to reading literacy requires engaging learning media to increase children's interest. However, the use of engaging learning media, particularly in Al-Hamzar Islamic Kindergarten, is still not optimal. The purpose of this study was to improve reading literacy skills by using pop-up books in Al-Hamzar Islamic Kindergarten with 17 children in class B, consisting of 10 girls and 7 boys. This study is a classroom action research (CAR) consisting of two cycles. Each cycle consists of planning, implementation, observation, and reflection, and each cycle is carried out with 3 meetings. The data collection techniques used are observation and documentation. The results of the study in the pre-cycle, cycle I, and cycle II are as follows: in the pre-cycle, the number of children who achieved the criteria for developing according to expectations (BSH) was 4 children or 24%. In cycle I, the number of children who achieved the criteria for developing according to expectations (BSH) and developing very well (BSB) was 9 children or 53%. In cycle II, 14 children, or 82.1%, met the criteria for developing as expected (BSH) and developing very well (BSB). Therefore, this study can be considered successful, meeting the minimum indicator of 75%.